Preseason body composition adaptations in elite white and Polynesian Rugby Union athletes - Zemski, A. J.; Keating, S. E.; Broad, E. M.; Marsh, D. J.; Hind, K.; Slater, G. J. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
During preseason training, rugby union (RU) athletes endeavor to enhance physical performance characteristics that are aligned with on-field success. Specific physique traits are associated with performance; therefore body composition assessment is routinely undertaken in elite environments. This study aimed to quantify preseason physique changes in elite RU athletes with unique morphology and divergent ethnicity. Twenty-two White and Polynesian professional RU athletes received dual-energy X-ray absorptiometry assessments at the beginning and conclusion of an 11-week preseason. Interactions between on-field playing position and ethnicity in body composition adaptations were explored, and the least significant change model was used to evaluate variations at the individual level. There were no combined interaction effects with the variables position and ethnicity and any body composition measure. After accounting for baseline body composition, Whites gained more lean mass during the preseason than Polynesians (2,425 ± 1,303 g vs. 1,115 ± 1,169 g; F = 5.4, p = .03). Significant main effects of time were found for whole body and all regional measures with fat mass decreasing (F = 31.1-52.0, p < .01), and lean mass increasing (F = 12.0-40.4, p < .01). Seventeen athletes (nine White and eight Polynesian) had a reduction in fat mass, and eight athletes (six White and two Polynesian) increased lean mass. This study describes significant and meaningful physique changes in elite RU athletes during a preseason period. Given the individualized approach applied to athletes in regard to nutrition and conditioning interventions, a similar approach to that used in this study is recommended to assess physique changes in this population.